Peran Dukungan Suami bagi Kesejahteraan Psikologis Jurnalis Perempuan - Riani Putriyani; Ratih Arruum Listiyandini (Lembaga Penelitian Universitas YARSI, 2018)
Married woman who are working as journalist have their own challenge to achieve optimal psychological well-being. This research aims to investigate how is the role of husband’s social support towards psychological well-being of female journalists. The study used quantitative approach and cross-sectional design. By snowball sampling method, research was conducted to 100 female journalist using adapted scale of psychological well-being (SPWB) and social support questionnaire constructed by the researcher. Based on regression analysis, social support from husband positively and significantly influence psychological well-being of female journalists, with mostly contributes to environmental mastery dimension and life purpose. Thus, it is imperative for female journalist husband to give support for their spouse in order to enhance the psychological well-being of female journalists.